CCR5 inhibition in colorectal cancer patients - Halama, Niels (Translational cancer research, 2016)
Immunotherapy in metastatic colorectal cancer is a challenge. I would like to thank Dr. Mukaida for his comprehensive commentary (1) on our work (2). A couple of points were raised that I will address in this letter. Immunotherapy with new immune checkpoint inhibitors is a different approach (3) compared to the immunotherapies based on vaccination or cytokine application. While for vaccination approaches no clear benefit was identified in colorectal cancer (4), combined chemotherapy with cytokines (GOLFIG trial) showed clinical effects, albeit at the price of autoimmune side effects (5). This situation highlights the complexities of immunotherapies quite well and shows that patients with microsatellite-instable colorectal cancer are a limited subgroup within colorectal cancer (6).
Gesehen am 26.03.2018